Guia para o sistema Africano de direitos humanos: Celebrando quarenta anos desde a adopção da Carta Africana de Direitos do Homem e dos Povos 1981 - 2021 - Centre for Human Rights, Faculty of Law, University of Pretoria (Pretoria University Law Press (PULP), 2021)
A Guide to the African human rights system has been conceived as an accessible and informative introduction to the human rights system established under the auspices of the African Union (AU). This Guide provides an overview of developments related to the African Charter on Human and Peoples' Rights, its supervisory body, the African Commission on Human and Peoples' Rights, the African Court on Human and Peoples' Rights, as well as the African Charter on the Rights and Welfare of the Child and its supervisory body, the African Committee of Experts on the Rights and Welfare of the Child. It is launched on 2 November 2017, commemorating the date, 30 years earlier, on which the African Commission was inaugurated. The Guide aims to both chart the most salient historical developments and provide an accessible introduction to the African human rights system, and is continuously revised. The Centre for Human Rights is both an academic department and a non-governmental organisation (NGO) accorded observer status with the African Commission. The Centre teaches academic programmes and engages in research, advocacy and training on human rights, with a specific focus on Africa. Its flagship programmes are the Master's in Human Rights and Democratisation in Africa and the African Human Rights Moot Court Competition. For more information on the Centre for Human Rights, visit www.chr.up.ac.za